2022
DOI: 10.1186/s12871-022-01699-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated effluent potassium concentrations predict the development of postreperfusion hyperkalemia in deceased liver transplantation: a retrospective cohort study

Abstract: Background Postreperfusion hyperkalemia (PRHK) has garnered increasing attention in regard to deceased liver transplantation (LT), especially for LT using the expanded criteria donor grafts. However, the impact of the effluent potassium (eK+) concentration on PRHK has been largely overlooked. We evaluated whether elevated eK+ concentrations are associated with PRHK in deceased LT. Methods In this single-institution, retrospective cohort study, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Higher donor BMI was significantly associated with PRS in a study by Bekki et al., where the PRS group had an average donor BMI almost 2 kg/cm 2 higher than the non‐PRS group 17 . Similarly, larger graft weight was associated with development of post‐reperfusion hyperkalemia in a study by Zhang et al 24 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Higher donor BMI was significantly associated with PRS in a study by Bekki et al., where the PRS group had an average donor BMI almost 2 kg/cm 2 higher than the non‐PRS group 17 . Similarly, larger graft weight was associated with development of post‐reperfusion hyperkalemia in a study by Zhang et al 24 …”
Section: Discussionmentioning
confidence: 92%
“…Higher donor BMI was significantly associated with PRS in a study by Bekki et al, where the PRS group had an average donor BMI almost 2 kg/cm 2 higher than the non-PRS group. 17 Similarly, larger graft weight was associated with development of post-reperfusion hyperkalemia in a study by Zhang et al 24 Kim et al found that underlying autonomic tone in transplant recipients played a role in the development of PRS. 20 In this study of 218 patients, they performed frequency domain analysis of heart rate variability which they utilize as a reflection of autonomic tone.…”
Section: Predictors Of Post-reperfusion Syndromementioning
confidence: 92%
See 1 more Smart Citation
“…However, the HTK solution has a relatively low potassium concentration compared to other preservative solutions employed in the transplant. The systemic spread of cytokines and eicosanoids can also be minimized by this technique 14 .…”
Section: Discussionmentioning
confidence: 99%
“…PRS was initially described as cardiovascular collapse following graft reperfusion during LT and was defined as a greater than 30% reduction in mean arterial pressure (MAP) relative to the baseline value within 5 min of reperfusion that lasts for at least 1 min 9 . The concept of severe PRS 6 8 , 10 12 has emerged since the increased utilization of expanded criteria donor (ECD) grafts worldwide, focusing on severe hyperkalemia 13 , 14 , significant arrhythmias 10 , refractory hypotension 10 12 , and even cardiac arrest 10 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%